Missing the Popular Vote: Pitfalls in US Democracy and Reform Proposals - Friedrich L. Sell; Jürgen Stiefl (Intereconomics)
Abstract Only a few years ago, it was a widespread belief that globalisation would trigger processes of democratisation worldwide. However, even old and established democracies such as the United States have recently revealed serious weaknesses. This article shows that the US election system is heavily distorted and recommends profound and transparent Electoral College reforms in the election of US presidents. Furthermore, the article highlights the implications the challenges facing American democracy have for Europe.